The significances of the final -h as a marker of entering tone characters in Romanized Chinese Texts in the Qing Dynasty. - Wong, Ling Yann (Science Press, 2009)
The significances of the final -h as a marker in Romanized Chinese texts in the Qing Dynasty can be summed up into three points as below: 1. the final -h is the marker of the entering tone; 2. The final -h does not have any independent meaning, neither the marker of tone category; 3.The final -h indicates a short intonation. Based on the pronunciation of entering tone chanlcters which noted in Romanized Chinese Texts in the Qing Dynasty I and the investigation and research of Modern Dialects, this article aims to discuss the significances of the final-h of entering tone characters which recorded by the Westerners to China in the nineteenth century.